Pengaruh Aktivitas Seksual Pranikah, Ketaatan Beragama dan Sosial Ekonomi terhadap Kehamilan Remaja di Kecamatan Saptosari Gunungkidul - Elly Magdalena; Hari Basuki Notobroto (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
Teenage pregnancies still prevalent in rural areas with a low levels of family income. Teenage pregnancy may cause maternal mortality and infant mortality. This study was conducted to analyze the risk factors of teenage pregnancy in the District Saptosari Gunungkidul. This research used analytical observational study with case control design. Data was collected by interview with 46 teenagers, consisted of 23 pregnant teenagers and 23 nonpregnant teenagers in Saptosari Gunungkidul. The samples were taken by simple random sampling method and interviews were conducted with respondents to get the information about the variables studied. The independent variable were premarital sexual activity, religious obedience and social economic. Dependen variable in this study was teenage pregnancy. Data was analyzed using binary logistic regression ( α 0.05 ). The result showed that there was influence of religious obedience on teenage pregnancy. Teenage with low religious obedience had high risk to have teenage pregnancy than those with high level of religious obedience with OR 57,8. Teenage with low social economic had high risk to have teenage pregnancy than those with high social economic (OR: 63,9). The conclusion of this research is risk factors which infl uence the occurrent off teenage pregnancy are religious obedience and social economic.